Predictors of Chest Wall Toxicity after Lung Stereotactic Ablative Radiotherapy. Issue 1 (January 2016) - Thibault, I.; Chiang, A.; Erler, D.; Yeung, L.; Poon, I.; Kim, A.; Keller, B.; Lochray, F.; Jain, S.; Soliman, H.; Cheung, P.
Abstract: Aims: To determine the incidence and predictive factors of rib fracture and chest wall pain after lung stereotactic ablative radiotherapy (SABR). Materials and methods: Patients were treated with lung SABR of 48–60 Gy in four to five fractions. The treatment plan and follow-up computed tomography scans of 289 tumours in 239 patients were reviewed. Dose–volume histogram (DVH) metrics and clinical factors were evaluated as potential predictors of chest wall toxicity. Results: The median follow-up was 21.0 months (range 6.2–52.1). Seventeen per cent (50/289) developed a rib fracture, 44% (22/50) were symptomatic; the median time to fracture was 16.4 months. On univariate analysis, female gender, osteoporosis, tumours adjacent (within 5 mm) to the chest wall and all of the chest wall DVH metrics predicted for rib fracture, but only tumour location adjacent to the chest wall remained significant on the multivariate model ( P  < 0.01). The 2 year fracture-free probability for those adjacent to the chest wall was 65.6%. Among those tumours adjacent to the chest wall, only osteoporosis ( P  = 0.02) predicted for fracture, whereas none of the chest wall DVH metrics were predictive. Eight per cent (24/289) experienced chest wall pain without fracture. Conclusions: None of the chest wall DVH metrics independently predicted for SABR-induced rib fracture when tumour location is taken into account. Patients with tumours adjacent (within 5 mm) to the chest wall are at greater risk of rib fracture after lung SABR, and among these, an additional risk was observed in osteoporotic patients. Highlights: Rib fractures are not uncommon after lung stereotactic ablative radiotherapy (SABR) for tumours adjacent to the chest wall. Almost half the SABR-induced rib fractures were symptomatic. None of the chest wall dose–volume histogram parameters independently predicted for rib fracture. For tumours adjacent to the chest wall, osteoporosis predicted for rib fracture.